The Zero-G headache - Elmer, Robert (Minneapolis, Minn. : Bethany Backyard, 2000)
When Zero-G, a hot new space-rock boy band, arrives at the space station, the AstroKids learn a valuable lesson about hospitality.
Keywords: Space stations; Christian life; Science fiction